THE EFFECTIVENESS OF USING PICTURE SERIES ON STUDENTS’ WRITING ACHIEVEMENT ACROSS LEARNING STYLE - Andrianto Arissaputra (Language-Edu, 2020)
This study attempted to examine the contribution of the usage of picture series for developing the students’ writing skill on producing recount text and the relationship between picture series and students’ learning style. The researcher chose two existing groups to become experimental group and control group. Picture series were used for teaching writing in experimental group. However, the researcher did not apply picture series in control group. After 6 meetings, researcher conducted posttest to see the picture series’ capability in improving students’ writing skill. The outcome was the students’ score taught by using picture series were significantly different than students taught without using picture series. For second objectives, the writer found out that visual students did not have better achievement in writing recount text than auditory students in both groups. Same with second objectives, because obtained significant value was higher than accepted significant value (0.491>0.05); it can be concluded that there is no effect between picture series and learning style toward students’ achievement on writing recount text.